Variation in blood biochemical constituents during post-partum period in crossbred cows - DHOBLE, R L; MANE, S D; SAWALE, A G; INGAWALE, M V (The Indian Journal of Animal Reproduction, 2023)
Recently normal parturited twenty cows were selected for this experiment. Ten cows in treatment and ten cows in control group were taken for this study. Blood samples were collected weekly from day of parturition up to 17th week of post partum period for estimation of blood glucose, serum cholesterol, serum protein and triglycerides. In results the values of glucose, cholesterol, protein and triglycerides at the time of parturition were declined. The values of glucose, cholesterol, proteins were higher during estrus period and the triglycerides were at normal level. After completion of uterine involution PGF 2 alpha treatment was given to all the 20 cows. These values of glucose, cholesterol protein was higher in pregnant cows in early gestation up to 17th week in postpartum period. The levels of all the constituents were normal level in non-pregnant cows. There was significant difference between pregnant and non-pregnant cows.